Measuring a Patient's understanding of their prognosis: An exploratory analysis. Issue 10 (19th August 2022) - Rosenfeld, Barry; Walsh, Leah E.; Zhu, Danqi; Cham, Heining; Polacek, Laura C.; Duva, Melissa M.; Applebaum, Allison J.
Abstract: Objective: In patients with cancer across the illness trajectory, treatment decisions are often influenced by one's perception of their prognosis (i.e., curability of disease, life expectancy, quality of life). However, research on how patients understand their prognosis (i.e., prognostic understanding) has been limited by simplistic measurement tools that fail to capture the complexity of the construct. This study describes the initial development of a measure of prognostic understanding: the Prognostic Understanding Perceptions Scale (PUPS) for use in patients with advanced cancer. Method: An initial pool of 16 candidate items were developed through semi‐structured interviews with 15 experts (oncology, psycho‐oncology and palliative care professionals) and 30 advanced cancer patients. We investigated the dimensionality, internal item structure, item difficulty and item discrimination of the item pool using exploratory factor analysis (EFA), classical test theory (CTT) and item response theory (IRT) analyses. Convergent and divergent validity were based on correlations between PUPS, terminal illness acknowledgement, and self‐report measures of depression, anxiety, hopelessness, and death acceptance. Results: The final measure was comprised of nine items encompassing three factors (perceived curability, illness trajectory, treatment options), yielding strong psychometric properties. Conclusion: These results provide preliminarily support for PUPS as a multifaceted measure of prognostic understanding developed for use in patients with advanced cancer. Preliminary findings also highlight the potential utility of the PUPS for clinical settings, as a means of enhancing communication between patients and physicians.